Upaya Guru Dalam Menanamkan Karakter Religius Siswa Melalui Program Keterampilan Agama di Madrasah Aliyah Negeri 5 Jombang - Lutfi Lailiya; Sholihul Anshori (JOURNAL SAINS STUDENT RESEARCH, 2024)
The religious skills program is a program designed to help students understand, apply, practice religious teachings and religious practices in everyday life. The researcher determined 3 research focuses including: 1) What is the Religious Character of MAN 5 Jombang, 2) How is the Religious Skills Program at MAN 5 Jombang, 3) What efforts are made by MAN 5 Jombang teachers to instill religious character in students through the religious skills program. Qualitative methods were used in this research with the type of case study research. Based on the data collected, this research uses observation, interviews and documentation methods. The results of this research are: 1) The religious character of students at MAN 5 Jombang is very good. Students' religious character is not only in worship but they also apply good manners in their behavior. 2) The religious skills program at MAN 5 Jombang is a program created to provide an in-depth understanding of Islamic religious teachings such as: prayer practice, memorizing letters, istighosah and tahlil, sermon practice, teaching tpq, polite behavior and other religious practices. 3) Efforts made by teachers to instill religious character in students through the religious skills program at MAN 5 Jombang, namely: teachers provide inspiration to students to continue to be active in studying religious knowledge, teachers provide material support, teachers educate students to carry out religious habits such as Duha prayers and praying Duhur together, teachers also get students used to reading the Al-Qur'an and Asmaul Husna every day, teachers accompany students in every activity, and teachers also get students used to always smiling, saying hello and greetings when they meet.